Instrumen Pengendalian Harga Beras di Indonesia: Waktu Efektif yang Dibutuhkan - Desi Aryani (Perum BULOG, 2021)
Rice is one of the main commodity forming inflation. The government always tries to maintain rice price stability at a certain level that benefits both farmers and consumers. Rice price stabilization policy instruments require a lag time to be effective in influencing the prices. This study aims to analyze the lag effective time required to control rice prices in Indonesia and to reviewing the rice price stabilization policy with the tinbergen framework approach. The study used time series secondary data with multiple linear regression analysis tools. The results of the analysis show that the time lag is not necessary for the rice HPP variable. The HPP of rice in period t has effectively affected the consumer's rice price. Market operation variable is ineffective at any lag, market operation cannot influence consumer rice prices at the national level because this policy is incidental. The rice import variable will have an effect on reducing consumer rice prices at lag 6, meaning that the decline in rice prices will be seen in the next six months. Mapping based on Tinbergen framework, exsogenous variables consist of: policy instruments (Rice HPP, Market Operation, Rice Import); constraints (timeliness of implementation, volume accuracy, rice quality, anti-competitive behavior of rice traders); and factors beyond control (extreme weather, damaged infrastructure). Endogenous variables include: goals for target variables (stability of consumer rice prices); and side effects (suppressing inflation, stable prices at the consumer level have an impact on price stability at the producer level, the fulfillment of stocks as CBP in Bulog's warehouses, consumers getting quality rice at appropriate prices). The ultimate goal is social welfare in the form of an increase in community welfare.